Application of Electrochemical Techniques and Mathematical Simulation in Corrosion and Degradation of Materials - González-Sánchez, Jorge; Canto, Gabriel; Dzib-Pérez, Luis; García-Ochoa, Esteban (IntechOpen, 2012)
None